The versatile amalgam: Interests and corruption in Russia-Venezuela relations - Alejandro Cardozo Uzcátegui; Víctor M. Mijares (European Review of Latin American and Caribbean Studies, 2020)
The Russia-Venezuela relations are the most controversial of those between Latin American states and extra-regional powers, due to the military-technical nature of its original links its implications for Russian-United States rivalry, and over the hemispheric security and democracy. This article explores these from the role of Russian-Venezuelan corruption as a versatile amalgam within the alliance from 2005 to 2018. Based on a descriptive research design, the systematization of scattered information, and the application of a congruence method, we infer that corruption contributes to improving Russian-Venezuelan political cohesion. Our inference indicates that these ties, in addition to serving Russian-Venezuelan geopolitical interests regarding the United States, constitute a cycle in which political corruption strengthens the alliance, favouring special corporate interests, undermining rule of law, encouraging corruption, and revitalizing authoritarianism in Venezuela.  Resumen: Una amalgama versátil: Intereses y corrupción en las relaciones ruso-venezolanas Las relaciones entre Rusia y Venezuela son las más controvertidas entre los estados latinoamericanos y las potencias extrarregionales, debido a la naturaleza técnico-militar de sus vínculos originales, sus implicaciones para la rivalidad ruso-estadounidense, y sobre la seguridad hemisférica y la democracia. Este artículo explora lo anterior desde el papel de la corrupción ruso-venezolana como una amalgama versátil dentro de la alianza entre 2005 y 2018. Basado en un diseño de investigación descriptivo, sistematización de información dispersa y aplicación de un método de congruencia, inferimos que la corrupción contribuye a mejorar la cohesión política ruso-venezolana. Nuestra inferencia indica que estos lazos, además de servir a los intereses geopolíticos ruso-venezolanos con respecto a los Estados Unidos, constituyen un ciclo en el que la corrupción política fortalece la alianza, favorece intereses corporativos especiales, socava el estado de derecho, fomenta la corrupción y revitaliza el autoritarismo en Venezuela.